Pembentukan Karakter Disiplin Peserta Didik Yang Berbasis Kemaritiman Melalui Kepemimpinan Multikultural - Dewi Sartika; Sitti Hartinah; Taufiqulloh (Universitas Pancasakti Tegal, 2020)
This study aims to create a maritime-based disciplinary character for students through multicultural leadership at SMK SUPM Yamipura Suradadi, Tegal Regency. The population and sample of this study were 30 students. The research method used in this research is quantitative quantitative analysis. Collecting data in this study using documentation and questionnaires. The data analysis that the writer uses is the proportional descriptive analysis technique and the t-test. The results showed that the disciplinary character of students before implementing multicultural leadership at SMK SUPM Yamipura Suradadi Tegal Regency was in the low criteria of 8 students (26.7%). While the disciplinary character of students after implementing multicultural leadership at SMK SUPM Yamipura Suradadi, Tegal Regency, is a high criterion of 12 students (40.0%). Multicultural Character formation is carried out in schools by utilizing school culture including: school artifacts, school ceremonies, school rules, values and beliefs. Multicultural Character Building is carried out in schools by utilizing school culture. School culture has a role in producing good work productivity for each individual and school work unit. From the results of the analysis, it was obtained the t-count value of 5.63. The tcount value is then consulted with t table at a significant level of 5% or ( 5%) with degrees of freedom N-1 or 30 - 1 = 29 where t table = 2.042 turns out that tcount = 5.63> t table = 2.042 which means that the null hypothesis is rejected. and accepting the hypothesis that reads "The formation of maritime-based disciplinary character of students can be improved through multicultural leadership at SMK SUPM Yamipura Suradadi, Tegal Regency